Ascochyta blights of grain legumes - Tivoli, Bernard; Baranger, Alain; Muehlbauer, Fred J.; Cooke, B. M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Ascochyta blights consistently affect large areas of grain legume production (pea, lentil, chickpea and faba bean) in all countries where they are cultivated. These diseases are capable of causing large yield losses under conducive environmental conditions. This book considers the state of the art by taking a comparative approach of Ascochyta blight diseases of cool season food and feed legumes. Topics considered are pathogen diversity, legume genetics and breeding, and integrated disease management. Reprinted from European Journal of Plant Pathology, Volume 119, No. 1, 2007 - B. Tivoli is a scientist in plant disease epidemiology at INRA (French National Institute of Agronomical Research), Le Rheu, France and member of AEP (European Association of Grain Legumes) and SFP (French Plant Pathology Society). - F. J. Muehlbauer is a geneticist and breeder of grain legumes at USDA Agricultural Research Service, Pullman, Washington, USA, and a member of the Crop Science Society of America, American Society of Agronomy, and AEP. - A. Baranger is a scientist in genetics of legumes at INRA (French National Institute of Agronomical Research), Le Rheu, France. - B. M. Cooke is a Professor of Plant Pathology and the Editor-in-Chief of the European Journal of Plant Pathology at the School of Biology and Environmental Science, University College Dublin, Ireland.
Foreword -- Towards identifying pathogenic determinants of the chickpea pathogen Ascochyta rabiei -- Biotic factors affecting the expression of partial resistance in pea to ascochyta blight in a detached stipule assay -- Validation of a QTL for resistance to ascochyta blight linked to resistance to fusarium wilt race 5 in chickpea (Cicer arietinum L.) -- Genetic relationships among Chickpea (Cicer arietinum L.) genotypes based on the SSRs at the quantitative trait Loci for resistance to Ascochyta Blight -- Inheritance of resistance to Mycosphaerella pinodes in two wild accessions of Pisum -- Comparison of the epidemiology of ascochyta blights on grain legumes -- Development of ascochyta blight (Ascochyta rabiei) in chickpea as affected by host resistance and plant age -- Assessment of airborne primary inoculum availability and modelling of disease onset of ascochyta blight in field peas -- Integrated disease management of ascochyta blight in pulse crops -- The sympatric Ascochyta pathosystems of Near Eastern legumes, a key for better understanding of pathogen biology -- Role of host specificity in the speciation of Ascochyta pathogens of cool season food legumes -- Diagnostics, genetic diversity and pathogenic variation of ascochyta blight of cool season food and feed legumes -- Resistance to ascochyta blights of cool season food legumes.
Keywords: Life sciences; Plant genetics; Plant pathology; Life Sciences; Plant Pathology; Plant Genetics & Genomics; Electronic books